แนวทางการบริหารจัดการสถานศึกษาเพื่อสร้างความเป็นพลเมืองโลกของ โรงเรียนในสังกัดองค์กรปกครองส่วนท้องถิ่นที่ตั้งบริเวณในเขตเมืองและชายขอบ Guidelines for school management to create global citizenship under local administrative organization in urban and ... - บุญธรรม พีรบูลย์; วิเศษศิริ ปองสิน (An Online Journal of Education, 2017)
การวิจัยครั้งนี้ มีวัตถุประสงค์ 3 ประการ คือ 1) เพื่อศึกษาสภาพปัจจุบัน 2) เพื่อศึกษาปัญหา และ 3) เพื่อหาแนวทางการบริหารจัดการสถานศึกษาเพื่อสร้างความเป็นพลเมืองโลกของโรงเรียนในสังกัดองค์กรปกครองส่วนท้องถิ่นที่เหมาะสม ประชากร คือ โรงเรียนที่ตั้งบริเวณในเมือง และโรงเรียนที่ตั้งบริเวณชายขอบของประเทศไทย ซึ่งกรอบการวิจัยใช้องค์ประกอบในการบริหารจัดการสถานศึกษาเพื่อส่งเสริมความเป็นพลเมืองโลก (Oxfam, 2015) ซึ่งประมวลผลและวิเคราะห์ข้อมูลวิจัยโดยการแจกแจงความถี่ ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัย มีดังนี้ (1) สภาพปัจจุบันโรงเรียนที่ตั้งในเมือง พบว่า ด้านบรรยากาศในโรงเรียนมี สภาพการปฏิบัติสูงสุด (Mean = 3.60) และด้านการพัฒนาบุคลากรมีสภาพการปฏิบัติต่ำสุด (Mean = 2.80) ผลรวมเฉลี่ย (Mean = 3.14) และสภาพปัจจุบันโรงเรียนที่ตั้งชายขอบ พบว่า ด้านบรรยากาศในโรงเรียนมีการสภาพการปฏิบัติสูงสุด (Mean = 3.55) และด้านการส่งต่อมีสภาพการปฏิบัติต่ำสุด (Mean = 2.73) ผลรวมเฉลี่ย (Mean = 3.07) (2) สภาพปัญหาโรงเรียนที่ตั้งในเมือง พบว่า ด้านการพัฒนาบุคลากรมีปัญหาในการปฏิบัติมากที่สุด คิดเป็นร้อยละ 49.68 และด้านการมีส่วนร่วมมีปัญหาน้อยที่สุด คิดเป็นร้อยละ 34.19 และสภาพปัญหาโรงเรียนที่ตั้งชายขอบ พบว่า ด้านการส่งต่อ และด้านการมีส่วนร่วมของชุมชนมีปัญหามากที่สุด คิดเป็นร้อยละ 44.00 และด้านการมีส่วนร่วมมีปัญหาน้อยที่สุด คิดเป็นร้อยละ 26.29 (3) แนวทางการบริหารจัดการสถานศึกษาเพื่อสร้างความเป็นพลเมืองโลกของโรงเรียนในสังกัดองค์กรปกครองส่วนท้องถิ่นที่ตั้งในเมือง ด้านพัฒนาบุคลากร คือ ผู้บริหารต้องเป็นผู้นำต้นแบบ ส่งเสริมสนับสนุนบุคลากรในด้านความเป็นพลเมืองโลก โรงเรียนที่ตั้งชายขอบ ด้านส่งต่อ คือ สถานศึกษาควรกำหนดแนวทางที่ชัดเจนและสร้างเครือข่ายระหว่างสถานศึกษา The purposes of this research were to (1) study the current state, (2) study the problems of, and (3) establish guidelines for the school management of promoting global citizenship of students in schools under the local administrative organization. The population consisted of the schools in urban and border areas in Thailand. The research framework was the Oxfam (2015) school management guidelines for encouraging global citizenship. The data were analyzed using descriptive statistics, i.e. percentage, mean and standard deviation. The findings were as follows: (1) The current state of urban schools are the school ethos is the highest state (Mean = 3.60), staff development was at the lowest state (Mean = 2.80) and the total average (Mean = 3.14). The border schools are School ethos is the highest state (Mean = 3.55) and the transition was at the lowest state (Mean = 2.73) and the total average (Mean = 3.07). (2) At the urban schools, staff development was the largest problem at a percentage of 49.68, and participation was the smallest problem at a percentage of 34.19. For border schools, the transition and community engagement are the biggest problems at a percentage of 44.00, and participation was the smallest problem at a percentage of 26.29 (3) The guideline for school management is to create global citizenship under local administrative organizations which are located in urban areas for staff development. Administrators need to be a model for staff to encourage and support them to embrace global citizenship. The guideline for schools in border areas regarding transition is the schools should set obvious guidelines and create school connections.